Управління людським потенціалом регіону через державну службу зайнятості: проблеми, тенденції, рішення - Пронін, Сергій Валерійович; Pronin, Serhii (ЦНТУ, 2025)
Мета роботи комплексне обґрунтування теоретичних засад, емпіричне оцінювання сучасного стану та розроблення практичних рішень щодо підвищення ефективності управління людським потенціалом регіону через діяльність державної служби зайнятості. The purpose of the work is to provide a comprehensive justification of the theoretical foundations, conduct an empirical assessment of the current situation, and develop practical solutions to improve the efficiency of human potential management in the region through the activities of the State Employment Service.
Management of human potential in the region through the state employment service: problems, trends, and solutions
Keywords: людський потенціал; регіональна політика зайнятості; служба зайнятості; human potential; regional employment policy; employment service